Nipa Palm (Nypa Fruticans) Improves the Storage Quality and Antioxidant Activity of Rice Cake (Sulgidduk): Nipa palm's effect of quality characteristics on rice cake(Sulgidduk) - Lee, Yu-Na; Youngsoon, Kim (Progress in Nutrition, 2021)
This study investigated the properties of nipa palm powder, upon addition to the traditional Korean food Sulgidduk. The samples were designed as N0 (without nipa palm powder), N1 (with 1% nipa palm powder), N2 (with 2% nipa palm powder), N3 (with 3% nipa palm powder), and N4 (with 4% nipa palm powder). The moisture content of the Sulgidduk samples increased as the amount of nipa palm powder increased. No significant difference was observed in the pH between samples. The total polyphenol and flavonoid contents were observed to significantly increase in the Sulgidduk samples as the amount of nipa palm powder increased. The hardness, cohesiveness, and chewiness of the samples decreased as the amount of nipa palm powder increased; however, the brittleness increased. Although sensory evaluation revealed that the overall preference was the greatest for the N0 samples, the N2 samples had the strongest retarding retrogradation effect.